Forbidden fruit: human settlement and abundant fruit create an ecological trap for an apex omnivore. (28th September 2016) - Lamb, Clayton T.; Mowat, Garth; McLellan, Bruce N.; Nielsen, Scott E.; Boutin, Stan
Summary: Habitat choice is an evolutionary product of animals experiencing increased fitness when preferentially occupying high‐quality habitat. However, an ecological trap (ET) can occur when an animal is presented with novel conditions and the animal's assessment of habitat quality is poorly matched to its resulting fitness. We tested for an ET for grizzly (brown) bears using demographic and movement data collected in an area with rich food resources and concentrated human settlement. We derived measures of habitat attractiveness from occurrence models of bear food resources and estimated demographic parameters using DNA mark–recapture information collected over 8 years (2006–2013). We then paired this information with grizzly bear mortality records to investigate kill and movement rates. Our results demonstrate that a valley high in both berry resources and human density was more attractive than surrounding areas, and bears occupying this region faced 17% lower apparent survival. Despite lower fitness, we detected a net flow of bears into the ET, which contributed to a study‐wide population decline. This work highlights the presence and pervasiveness of an ET for an apex omnivore that lacks the evolutionary cues, under human‐induced rapid ecological change, to assess trade‐offs between food resources and human‐caused mortality, which results in maladaptive habitat selection. Abstract : The authors tested for an ecological trap (ET) in south‐east British Columbia where human settlement and rich grizzly bear habitat overlap. Bears occupying the ET faced survival consequences, which produced source–sink dynamics with far‐reaching effects. To date, this is the most rigorous test of an ET for a large mammal.